Analisis Kontribusi dan Laju Pertumbuhan Pajak Restoran terhadap pendapatan asli daerah kota Ambon - Pattimahu, Angel Merlyn (Journal of Applied Accounting, 2025)
In Law Number 28 of 2009 on Regional Taxes and Levies, local governments are granted the authority to explore financial resource potentials by establishing new types of taxes and levies not previously regulated, provided they meet the established criteria and reflect the aspirations of the community. Regional taxes, as one of the components of Local Revenue (PAD), are used to finance various regional expenditures, both routine and for development purposes. Regional taxes are expected to be a vital source of financing for government administration and regional development, as well as contribute to the improvement and equitable distribution of community welfare. Regional taxes are divided into two main categories: provincial regional taxes and regency/city regional taxes. This study aims to determine the contribution and growth rate of restaurant taxes in Ambon City. The research method used is descriptive quantitative analysis, particularly in describing the results of calculations of the contribution and growth rate of restaurant taxes in the local revenue of Ambon City. The research object is the Ambon City Regional Revenue Office. This study shows that the contribution of restaurant taxes over the last five years (2020-2024) has fluctuated, with a significant increase in the growth rate in 2022, but a sharp decline in the following year. The study indicates that the Ambon City government has not been able to maintain and increase the contribution of restaurant taxes in the last five years. This is due to the lack of active involvement from officers in collecting taxes and in socializing the sanctions and payment procedures to the community, particularly to restaurant entrepreneurs. Keywords: Restaurant Tax, Contribution, Growth Rate, Local Revenue (PAD)